Estrogen catechols detection as biomarkers in schistosomiasis induced cancer and infertility - Botelho, M.C. (2017)
Urogenital schistosomiasis is a chronic infection caused by the human blood fluke Schistosoma haematobium. Schistosomiasis haematobium is a known risk factor for cancer leading to squamous cell carcinoma of the urinary bladder (SCC). This is a neglected tropical disease endemic in many countries of Africa and the Middle East. Schistosome eggs produce catechol-estrogens. These molecules are metabolized to active quinones that cause alterations in DNA (leading in other contexts to breast or thyroid cancer). Our group have shown that schistosome egg associated catechol estrogens induce tumor-like phenotypes in urothelial cells, originated from parasite estrogen-host cell chromosomal DNA adducts and mutations. Here we review recent findings on the role of estrogen-DNA adducts and how their shedding in urine may be prognostic of schistosome infection and/or represent potential biomarkers for urogenital schistosomiasis associated bladder cancer and infertility.